Conceptual Analysis of the Basic Education Laws Amendment Act and Its Implications for Diversity and Inclusion - Kanyopa, Theresia Joakim; Chibaya, Solomon (Journal of Posthumanism, 2025)
The ideas of diversity and inclusion have become prevalent throughout literature, with their expression included in various legislations. This paper presents a conceptual analysis of the Basic Education Laws Amendment Act focusing on its implications on diversity and inclusion in a changing South African legislative landscape. The critical theory underpinned the study to evaluate the Acts’ potential impacts on enhancing equal access to quality basic education. Research synthesis methods employed the qualitative research approach to identify broad themes and related subthemes across these studies in relation to the BELA Act. The review used systematic methods to identify research studies that examined how the BELA Act influences issues of diversity and inclusion. The Thematic analysis identified three themes: (1) The role of the BELA Act in addressing equity and access to quality education (2) Impact of the BELA Act on parental involvement and community engagement in basic education (3) The implications of the BELA Act for diversity and inclusion in basic education. This literature review highlights the ongoing tensions between the Department of Basic Education and South African schools in implementing policies that promote diversity and inclusion in education. The findings suggest that while the BELA Act introduces progressive measures to promote inclusivity, challenges remain in policy implementation, stakeholder resistance, and schools’ systemic inequalities. The study concludes with recommendations for enhancing the practical application of the Act to foster a more inclusive and equitable basic education system in South Africa.